Penerapan Prinsip Tata Kelola Perusahaan Yang Baik Di Sekretariat DPRD Kabupaten Jombang - Rahmat Danang Anggartawan; Anggi Sri Wahyuni; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
The model of good corporate administration decides the methodology for the organization so that benefits generally increment esteem and keep up with the business progression development process. As a result, in order for any business to reap the benefits of good corporate governance, it is necessary for it to keep working on improving. The company should have a solid foundation for running its business if the good governance principles are followed seriously. Investors will have a greater trust in the company on the outside, which will raise the share price. Accomplices likewise make it a point to greater business connections. In order to offer the best prices and improve the company's efficiency, suppliers adhere to clear rules and believe they will be treated fairly. Banks likewise have high trust in expanding credit that might be required for business extension.